Shariah Compliance, Trust, and Perceived Risk in Digital Islamic Banking: Evidence from Millennial and Gen-Z Users - Sukri, Saipul Al; Prihastuti, Asepma Hygi; Nuryanti, Nuryanti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The development of digital Islamic banking in Indonesia has grown rapidly, yet its adoption level remains below market potential. This study aims to examine the influence of trust, perceived risk, and shariah compliance on users’ adoption intention toward digital Islamic banking services. A quantitative approach was employed through a survey of 200 respondents who had used or were familiar with Islamic digital banking applications. Data were analyzed using linear regression with SPSS. The results show that trust and shariah compliance have a significant positive effect on adoption intention, while perceived risk has a significant negative effect. Shariah compliance emerges as the most dominant factor, indicating that adherence to Islamic principles remains a central determinant of users’ decisions in adopting digital financial services. These findings confirm that adoption of digital Islamic banking is shaped not only by technological aspects but also by value-based considerations, security perceptions, and trust in the service provider.Keywords: digital Islamic banking, trust, perceived risk, shariah compliance, adoption intention.